ANALISIS TINGKAT PEMAHAMAN MAHASISWA TERHADAP KONSEP DASAR AKUNTANSI - Eko Febri Lusiono (JURNAL RISET TERAPAN AKUNTANSI, 2017)
The aims of Research Analysis Student’s Understanding Level about Basic Concepts of Accounting (Empirical Study on Registered Poltesa students had taken Basic Accounting Subject) are to measuring difference of comprehension and how student’s of Poltesa comprehension based on their background education (SMK / SMA / MA). Total respondens 155 students in 2014 using Kruskal Wallis test. Based on hypothesis test, assets andliabilities variables in chi-square table statistic counted 41,784 > chi-square counted 1,089 and 41,784 > chi- square counted 1,026, probability significant value counted 0,395 > 0,05 and 0,708 > 0,05 then H1 and H2REJECTED. There’s no significant difference about student’s comprehension of assets and liabilities concepts,equity variable in chi-square table statistic counted 41,784 > chi-square counted 9,521, probability significantvalue counted 0,021 > 0,05 then H3 ACCEPTED. Theres significant difference about student’s comprehension of equity concepts based on their background education. Based on that, students from SMK had the highest comprehension value of three variables. It concludes student’s from SMK more understand about Basic Concepts of Accounting. Therefore, student’s background education very influencing to take Basic Accounting subject at Poltesa.